The Validity and Practicality of the SETS-Based (Science, Environment, Technology, and Society) Interactive E-Book of Thermochemistry - M Anwar; Alimin; Munawwarah (Universitas Pendidikan Ganesha, 2023)
Validity and practicality are important elements in an e-book because it shows the accuracy and feasibility of the teaching material before it is used. This study aimed to determine the validity and practicality of teaching materials in interactive e-books based on SETS (Science, Environment, Technology, and Society) on thermochemical materials. The validity and practicality of the e-book are essential to study as the teaching materials developed are suitable for use in the learning process. This interactive e-book was developed through several stages using the DDE model development by Richey, Klein, and Nelson combined with 4STMD (Four Steps Teaching Material Development). Two validations were carried out, namely content validation and media validation. Both validations are in the very valid category. The practical aspect was obtained from a limited trial on teachers and students in a private school in Makassar. The test results on the teacher are in a good category, and the test results on the students are in the good category. The validity and practicality of the e-book show that this teaching material is feasible to use.